Apitan: Pelestarian Tradisi Agraris Lokal Masyarakat Jawa - Heri Dwi Santoso (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2013)
Agrarian activiites in Javanese communities cannot be separated yet from traditional rituals, which have been held for generations. One of those activities is Sedekah Bumi (earth’s alms). In some areas in Central Java, people use the term ‘apitan’ meaning an event held in Apit (the eleventh month in the Javanese Calendar). This research question deals with what philosophy being apitan that can make this ritual survives. The research was conducted in Trongso Hamlet, Ketangirejo Village, Grobogan Regency, Central Java Province. Method used in this research was qualitative research, combining quantitative data (in form of demographic data) with qualitative data (in form of data of observation and interview. The research showed that apitan is a way of expressing people’ gratitudes towards God, for the harvest.